2021
DOI: 10.3389/fvets.2021.662504
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Fluid Administration and the Coagulation System

Abstract: Intravenous fluid administration in veterinary patients can alter coagulation function by several mechanisms. Both crystalloid and colloid fluids cause hemodilution, reducing platelet count and plasma coagulation protein concentrations. Hemodilution is associated with a hypercoagulable effect at low dilutions and a hypocoagulable effect at higher dilutions. Composition of crystalloid fluids likely has a minor effect, primarily dependent on fluid ion composition. Hypertonic crystalloids may also cause hypocoagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…Although crystalloids can dilute coagulation factors, hypercoagulability can also be observed [ 21 ] because of the probable dilution of anticoagulant factors [ 45 ] as well as an increase in BMBT and a reduction in platelet count without reducing platelet aggregation [ 21 ]. However, the literature refers to blood dilutions above 20% of 0.9% NaCl in the blood, that is, in 1:4 mixtures [ 45 ], which is an extremely high volume compared to that used in the surgical groups in our study, with fluid therapy introduced at 10 mL/kg/h [ 22 ] for an average total surgical time of 57.4 ± 2.04 min.…”
Section: Discussionmentioning
confidence: 99%
“…Although crystalloids can dilute coagulation factors, hypercoagulability can also be observed [ 21 ] because of the probable dilution of anticoagulant factors [ 45 ] as well as an increase in BMBT and a reduction in platelet count without reducing platelet aggregation [ 21 ]. However, the literature refers to blood dilutions above 20% of 0.9% NaCl in the blood, that is, in 1:4 mixtures [ 45 ], which is an extremely high volume compared to that used in the surgical groups in our study, with fluid therapy introduced at 10 mL/kg/h [ 22 ] for an average total surgical time of 57.4 ± 2.04 min.…”
Section: Discussionmentioning
confidence: 99%
“…The second premise for our hypothesis of more hypocoagulability with HES was based on other, non-dilutional, mechanisms by which HES can cause hypocoagulability [ 7 ]. These include platelet dysfunction, [ 27 ] deficiency of vWF and FVIII, [ 13 ] generalized coagulation factor deficiencies, [ 28 ] altered fibrin meshwork structure [ 29 ] with impaired crosslinking, [ 30 ] and enhanced fibrinolysis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant changes over time were detected, with increasing PT and decreasing coagulation factor activities suggesting a pattern towards hypocoagulability in both groups. Both HES and crystalloid fluids can cause a dilutional coagulopathy proportionate to the degree of hemodilution [ 7 , 8 ]. It is likely that hemodilution increased over time in our study due to the administration of bolus study fluid and other fluid therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, signs of DIC were observed in seven dogs with AKI, one dog with CKD, and one dog with protein-losing nephropathy. In addition, dilution due to previous fluid therapy can also increase the coagulation time, especially in oliguric patients [12].…”
Section: Coagulation Timesmentioning
confidence: 99%